Real Person Fiction in Social Media - Heriyati, Nungki (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The study attempts to examine fiction derived from real person in social media which focuses on Instagram. The study requires textual analysis across the boundaries of fact, fiction, and affective features. Drawing on cognitive narrative and cultural theory especially fan studies the article attempts to examine fan practices in real person fiction especially in social media. The development of social media that exposes the daily life of celebrity enables fans to access their idols’ private life. Fans also like to write a fiction about their idol as a way to fill in the gap of the story they do not know or to construct their own version story about their idol. The Analysis shows that the practices of real person fiction include storying the event and creating the character of a real person. This involves selecting events, interviews, pictures, and then makes it up into a story. The story mixes up facts and the fans’ viewpoint. All of which are constructed beyond the boundary of facts to inventing facts. The practices are still debatable concerning the ethical matter. However, it cannot be denied that fanfiction on a real person signifies the development of a new narrative.